The golden dagger - Sempio, Antonio G.; Reyes, Soledad S. (Manila De La Salle University Publishing House, 2016)
"The Golden dagger revolves around Dalisay, a beautiful woman from the barrio, and the interconnected series of tragedies that befall her. The novel depicts her slow but almost inexorable descent into madness as she loses her sweetheart, her only means of livelihood, her mother, and her son due to the machinations of Don Sergio, the powerful father of her faithless sweetheart. She seeks to exact revenge but is eventually defeated by the conspiracy of forces around her. This novel is a gritty delineation of love determined by insidious sociopolitical forces reflective of the tensions in Philippine society in the 1930s"--Back cover.
Keywords: Poor women -- Philippines -- Fiction; Revenge -- Fiction; Social conflict -- Philippines -- Fiction